Changes in ferroelectric properties of lead indium niobate-lead titanate ceramics under compressive stress applied perpendicular to an electric field - Muangjai Unruan (2018)
The influences of perpendicular compressive stress on the ferroelectric properties of (1 - x)Pb(In1/2Nb1/2)O3-xPbTiO3 (x = 0.1 - 0.4) ceramics were investigated in this study. In general, with increasing compressive stress the coercive field and the dissipation energy of the ceramics were seen to increase. The stress-induced changes in the polarization, however, depended significantly on ceramic compositions. The observations were mainly interpreted in terms of competing influence of the domain switching through non-180° domain walls, clamping of domain walls, and the stress-induced decrease in the switchable part of spontaneous polarization. © 2009 Elsevier B.V. All rights reserved.